2012
DOI: 10.1093/icvts/ivs455
|View full text |Cite
|
Sign up to set email alerts
|

Potassium-induced conversion of ventricular fibrillation after aortic declamping

Abstract: The results from this register study demonstrate that potassium infusion is an effective and convenient first-hand measure to convert post declamping VF on CPB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…Although several studies have described successful chemical conversion of VF during cardiopulmonary bypass using potassium, successful chemical conversion of VF during conventional CPR has been seldom addressed. Interestingly, 50% of the K‐lido group animals achieved ROSC without electrical countershock in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have described successful chemical conversion of VF during cardiopulmonary bypass using potassium, successful chemical conversion of VF during conventional CPR has been seldom addressed. Interestingly, 50% of the K‐lido group animals achieved ROSC without electrical countershock in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that inducing transient cardiac standstill by infusing a high concentration of potassium allows successful cardioversion of VF during cardiopulmonary bypass . In a study that included 8,456 adult patients undergoing cardiac operations on cardiopulmonary bypass, Almdahl et al . reported that 79% of patients with VF after aortic declamping were successfully treated with 20 mmol potassium infusion.…”
mentioning
confidence: 99%
“…The mechanism of ventricular fibrillation appearing at that time is not precisely understood. It is well known that many factors contribute, such as electrolyte and acid disturbances or gradients, conduction abnormalities and more importantly inadequate myocardial preservation may play a role [3]. The best method must be developed for protection of the heart from myocardial injury during open heart surgery [4].…”
Section: Discussionmentioning
confidence: 99%
“…The stabilizing effect of potassium on ventricular fibrillation after declamping of the aorta has been much studied previously [15]. Sven M. Almdahl et al demonstrated that potassium infusion is an effective and convenient first-hand measure to convert post declamping VF on CPB [3]. Marcus L Koller et al, in an experimental model, demonstrated the anti-fibrillatory effect of hyperkalaemia on sustained VF.…”
Section: Discussionmentioning
confidence: 99%
“…4 Multiple investigators have studied extended potassium cardioplegia combined with cardiopulmonary bypass to treat or reverse refractory arrest and associated ischemia after cardiac surgery. 5-8 Treatment with combined cardiopulmonary bypass and potassium cardioplegia has also been studied for induced VF without surgery. 9 Provision of cardiopulmonary bypass during the treatment of spontaneous cardiac arrest is feasible, but challenging.…”
Section: Introductionmentioning
confidence: 99%